2000
DOI: 10.1080/036107300243650
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in Microvessel With Age in the Hippocampus of Senescence-Accelerated Mouse (SAM)-P/10

Abstract: Microvessels in the hippocampus of aged SAM-P/10 (14 months old) showed the following ultrastructural changes compared with those of young-mature controls (3 months old): (1) the majority of capillaries had lost the smooth contours typical of young cases; (2) the luminal surface of capillaries showed irregularity; (3) the endothelial cytoplasm was thicker; (4) vesicles appeared more frequently in the endothelium; (5) interendothelial tight junctions and basement membranes, however, seemed to show no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In addition to changes in mitochondrial content, BEC luminal surface projections, or pseudopods, were observed to vary in size and number during ageing, when analysed by 3D reconstruction in the cortex only. These results are consistent with previous studies that showed large luminal projections on BECs of senescence-accelerated mice, although this same study described them in hippocampal vessels and no quantitative analysis was carried out (Lee et al, 2000). BEC pseudopod-like microstructures have also been reported under inflammatory conditions in injured mouse BBB during encephalomyelitis (Lossinsky et al, 1991), and more recently in cultured human microvessel endothelial cells stimulated with chemokines such as CCL5 (Whittall et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition to changes in mitochondrial content, BEC luminal surface projections, or pseudopods, were observed to vary in size and number during ageing, when analysed by 3D reconstruction in the cortex only. These results are consistent with previous studies that showed large luminal projections on BECs of senescence-accelerated mice, although this same study described them in hippocampal vessels and no quantitative analysis was carried out (Lee et al, 2000). BEC pseudopod-like microstructures have also been reported under inflammatory conditions in injured mouse BBB during encephalomyelitis (Lossinsky et al, 1991), and more recently in cultured human microvessel endothelial cells stimulated with chemokines such as CCL5 (Whittall et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…The BBB of cortical capillaries appeared to undergo more age-related ultrastructural alterations than that of hippocampal capillaries. Although previous studies have reported a sensitivity of hippocampal vessels to ageing (Lee et al, 2000;Lourenço et al, 2018;Topple et al, 1991), a recent study in aged male mice has shown cortical blood vessels to be more strongly affected by cholinergic denervation than those in hippocampus (Nizari et al, 2019), which might have important consequences in age-related vasculopathies including BBB disruption.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Aging is associated with changes in microvascular plasticity and a reduced microvascular density (Amenta et al, 1995; Sonntag et al, 1997, 2000; Lynch et al, 1999). In addition, aging causes a progressive increase in microvascular abnormalities that affect blood-brain barrier function, including surface irregularities (Lee et al, 2000), thickening of the basement membrane and fibrous collagen deposits in the capillary wall (Burns et al, 1981; Keuker et al, 2000). Such abnormalities may decrease perfusion of the brain, leading to a decrease in nutrient and oxygen supply, which may be an important component in the development of age-related cognitive impairment (De Jong et al, 1997; Farkas et al, 2000, 2007; Farkas and Luiten, 2001; Riddle et al, 2003) and render the brain vulnerable to degenerative mechanisms.…”
Section: Introductionmentioning
confidence: 99%